Indonesian university students’ self-regulated writing (SRW) strategies in writing expository essays - Umamah, Atik; Cahyono, Bambang Yudi (Universitas Pendidikan Indonesia, 2020)
This research is carried out to investigate Indonesian EFL students’ use of self-regulated writing (SRW) strategies and to identify the SRW strategies applied, particularly by proficient students in writing. The research involved 45 students who have passed an essay writing course focusing on expository essays. Data on the students’ use of SRW strategies came from a Self-Regulated Learning Strategy Questionnaire (SRLSQ) adopted from Abadikhah et al. (2018). The students’ use of SRW strategies were categorized into six dimensions: motive, method, time, performance, physical environment, and social environment. Out of the total number of respondents, four proficient students were involved in a semi-structured interview. The interview was aimed at knowing the students’ use of SRW strategies in the planning, execution, and evaluation (PLEE) cyclical model of process writing. The result of the questionnaire data analysis showed that the students use all of the six dimensions of SRW strategies, with the highest mean for the social environment dimension and the lowest mean for the motive dimension. The result of the interview data analysis revealed that the proficient students also use the six dimensions of SRW strategies. Still, they dominantly apply the method, performance, and social environment dimensions of SRW strategies.